Assessment of Microvessel Permeability in Murine Atherosclerotic Vein Grafts Using Two-Photon Intravital Microscopy - Baganha, Fabiana (Int J Mol Sci, 2020)
Plaque angiogenesis and plaque hemorrhage are major players in the destabilization and rupture of atherosclerotic lesions. As these are dynamic processes, imaging of plaque angiogenesis, especially the integrity or leakiness of angiogenic vessels, can be an extremely useful tool in the studies on atherosclerosis pathophysiology. Visualizing plaque microvessels in 3D would enable us to study the architecture and permeability of adventitial and intimal plaque microvessels in advanced atherosclerotic lesions. We hypothesized that a comparison of the vascular permeability between healthy continuous and fenestrated as well as diseased leaky microvessels, would allow us to evaluate plaque microvessel leakiness. We developed and validated a two photon intravital microscopy (2P-IVM) method to assess the leakiness of plaque microvessels in murine atherosclerosis-prone ApoE3*Leiden vein grafts based on the quantification of fluorescent-dextrans extravasation in real-time. We describe a novel 2P-IVM set up to study vessels in the neck region of living mice. We show that microvessels in vein graft lesions are in their pathological state more permeable in comparison with healthy continuous and fenestrated microvessels. This 2P-IVM method is a promising approach to assess plaque angiogenesis and leakiness. Moreover, this method is an important advancement to validate therapeutic angiogenic interventions in preclinical atherosclerosis models.